2012
DOI: 10.1088/0741-3335/55/1/014002
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the flows and radial electric field in the HSX stellarator to neoclassical calculations

Abstract: Intrinsic flow velocities of up to ∼20 km s −1 have been measured using charge exchange recombination spectroscopy (CHERS) in the quasi-helically symmetric HSX stellarator and are compared with the neoclassical values calculated using an updated version (Lore 2010 Measurement and Transport Modeling with Momentum Conservation of an Electron Internal Transport Barrier in HSX (Madison, WI: University of Wisconsin); Lore et al 2010 Phys. Plasmas 17 056101) of the PENTA code (Spong 2005 Phys. Plasmas. 12 056114). P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 19 publications
1
31
1
Order By: Relevance
“…This mechanism could explain the decrease in I tor ðt ¼ 1Þ with increasing ECRH power. However, data from Charge Exchange Recombination Spectroscopy (ChERS) 27 shows no indication of such a large radial electric field, although this measurement is unable to adequately resolve the magnitude of the radial electric field very close to the magnetic axis because of the finite width of the neutral beam that is employed.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…This mechanism could explain the decrease in I tor ðt ¼ 1Þ with increasing ECRH power. However, data from Charge Exchange Recombination Spectroscopy (ChERS) 27 shows no indication of such a large radial electric field, although this measurement is unable to adequately resolve the magnitude of the radial electric field very close to the magnetic axis because of the finite width of the neutral beam that is employed.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Thus, a nonzero dΦ 0 /dψ gives a singular perturbation to the dΦ 0 /dψ = 0 limit in this partial trajectory model: the dΦ 0 /dψ = 0 solution for f a1 need not satisfy (23) can also be seen from the fact that when the dΦ 0 /dψ terms inẋ a andξ a are retained in the more accurate trajectories (17), these terms precisely cancel (23).…”
Section: Particle and Energy Moment Equations Conservation Propmentioning
confidence: 98%
“…With regard to the electrons, it was found that there were no major differences in core electron transport between the Standard configuration and Increased Iota configurations at W7-X due to the mitigating presence of a positive radial electric field 55,56 . At HSX the role of the radial electric field 57,58 in mitigating transport is still an open question. Finally, EMC3-EIRENE simulations contain no information about potential core neoclassical transport changes that may have occurred as a result of the change in magnetic configuration (i.e.…”
Section: Final Considerations and Conclusionmentioning
confidence: 99%